Biotic stress management in tomato : biotechnological approaches - Solankey, Shashank Shekhar; Shamim, Md., 1985- (Palm Bay, FL : Apple Academic Press, 2022)
"Biotic Stress Management in Tomato: Biotechnological Approaches highlights biotechnological tools and their utilization for biotic stress management in the tomato plant, one of the world's most important vegetable crops consumed by us in our daily diet and which is vulnerable to over 200 diseases as well as the impact of global climate change. The chapters cover the major diseases of tomato along with practical biotic stress management strategies through biotechnological and molecular approaches. The focus is on molecular tools that can be used to prevent or mitigate damage from such diseases as bacterial wilt, bacterial canker, damping off seedlings, late blight, early blight, fusarium wilt, septorial leaf spot, cercospora leaf spot, verticilium wilt, tomato leaf curl virus, tobacco mosaic virus, tomato spotted wilt virus, root knot nematode, fruit borer, sucking pests. Gene stacking/pyramiding and postharvest management strategies are also systematically discussed. This book provides an up-to-date and comprehensive review that will be a greatly useful resource, containing basic facts and information on the new and recent discoveries for biotic stresses management of tomatoes"--
Chapter 1. -- Tomato diseases, their impact, and management -- Chapter 2. -- Molecular tools for bacterial wilt resistance in tomato -- Chapter 3. -- Molecular methods for the controlling of damping off seedlings in tomato -- Chapter 4. -- Molecular methods for the controlling of late blight in tomato -- Chapter 5. -- Molecular approaches of early blight resistance breeding -- Chapter 6. -- Molecular approaches for the control of septoria leaf spot in tomato -- Chapter 7. -- Molecular approaches for the control of cercospora leaf spot in tomato -- Chapter 8. -- Molecular approaches for the control tomato leaf curl virus (TLCV) -- Chapter 9. -- Molecular advances of the tobacco mosaic virus infecting tomato -- Chapter 10. -- Molecular approaches to control the root-knot nematode in tomato -- Chapter 11. -- Molecular approaches for the control of fruit borer in tomato -- Chapter 12. -- Molecular approaches for control of sucking pest in tomato -- Chapter 13. -- Molecular approaches for multiple genes stacking/pyramiding in tomato for major biotic stress management -- Chapter 14. -- Molecular approaches for the postharvest losses in tomato by different biotic stresses.
Includes bibliographical references and index.
Also available online.
Keywords: Tomatoes -- Diseases and pests; Tomatoes -- Diseases and pests -- Control; Tomatoes -- Effect of stress on; Tomatoes -- Molecular aspects; Tomatoes -- Biotechnology